Butler's British Political Facts
VIII, 883 p.
Keywords: This book is the most comprehensive single volume reference work available for British political facts. Covering the period from 1900 to the present, it is the latest edition in a series previously edited by David Butler and various collaborators. This new edition updates the contents to the immediate post-European Union referendum period in the UK. It is useful to a wide range of potential readers, including students, educators, journalists, policy professionals, and anyone with an interest in politics and political history. It will be valuable to academics working in a variety of disciplines, including history and political science.